DIAGNOSTIC ACCURACY OF HEMATOLOGICAL INDICES FOR DIFFERENTIATION OF BETA THALASSEMIA TRAIT AND IRON DEFICIENCY ANEMIA – A CROSS SECTIONAL STUDY (The Research of Medical Science Review, 2025)
Objective: To check diagnostic accuracy of reliable hematological indices for differentiation between beta thalassemia trait and iron deficiency anemia in pediatric patients Methodology: This Cross-sectional study was conducted at Department of Pediatric, KRL Hospital, Islamabad Pakistan during July 2024 to December 2024. Children of age 2-12 years with microcytic anemia (Hb < 12.0 md/dL and low MCV < 74 fL) presenting to Pediatric OPD or admitted in pediatric wards were included. Blood complete picture for hemoglobin, MCV, RBC count, serum ferritin levels and Hb electrophoresis advised in all children. Diagnostic accuracy metrics of hematological indices including Mentzer index (MI), RBC count, RDW index, Srivastav Index (SI), Sirdah index, Ehsani Index (EI), England and Fraser index (EFI) and Ricerca Index (RI) were checked for detecting and differentiating type of anemia. Results: From 377 children with microcytic anemia, 240 (63.7%) were confirmed to have iron deficiency anemia (IDA) while 137 (36.3%) were confirmed as having Beta Thalassemia trait (BTT). The mean Hb of IDA and BTT children were 9.23 ± 0.83 and 9.62 ± 0.83 respectively (p=0.652), whereas MCV was 63.08 ± 4.37 and 58.23 ± 5.20 fL, respectively (p=0.011). Statistically significant difference was noted in RBC count and serum ferritin levels between IDA and BTT diagnosed children (p<0.005). The sensitivity ranged from 68.75% (Srivastav Index) to 95.83% (Ricerca Index), while specificity varied between 43.79% (Ricerca Index) and 76.64% (Ehsani and Sirdah Indices) with the Ehsani Index demonstrating the highest accuracy (79.56%). Conclusion: Ricerca Index had highest sensitivity 95.83% whereas Ehsani and Sirdah Indices had highest specificity of 76.64%.